(3GdaQjO aj EYQGH GdbQBf GdeLjOs - (3GdoerfnJnLH rHf nCpHj GdYqR rHf QTjO, efJLH GdOjf CHh jhSa GdgePGfj, GdebQF,J (B643 (3g` s
(3ChdgG (B:s
(3hHYO, aEf CaVd GdYdhe Yde cJGH Gddg GdPj gh eLeY GdYdhe GdTQjaI s
(3BNQgG (B:s
(3hHGdJGA Ydi eYfi CfJ hge Ydi JZdjH GdeNGWH, hgPG CYe ef GdjGA hgPG BNQ EYQGH ShQI ghO s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B290 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B7s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B238 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B123s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
Keywords: (3GdfMhs